Questioning an "icon of change": the Nuruosmaniye complex and the writing of Ottoman Architectural history - Suman, Fatma Selva. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
Eighteenth-century Istanbul set the stage for important political and socio-economic transformations; changing tastes and lifestyles were accompanied by an intensive architectural activity and more diffused patronage patterns. The climate of change was reflected on the urban environment where a more hybrid vocabulary started to emerge with wider penetration of foreign forms and novelties. This study focuses on the Nuruosmaniye that stands out as the first royal religious complex displaying baroque and neo-classical elements and a horse-shoe shaped courtyard which is unique in Ottoman architectural history. It aims to analyze the novelty of this prominent building within the dynamics of the eighteenth century and how it was perceived in contemporary local and foreign accounts. Hybridity in the architectural idiom, which is mostly of western origin, raised arguments around the “declinist” discourse and there are references to the interpretations of traditional scholarship on these largely accepted paradigms of “riseand- decline” and the notion of the “Tulip Period” in relation with the westernizing aspirations of the society and the innovative style of the Nuruosmaniye. The image of the building is addressed in this context, questioning the way it was construed as an “Icon of Change” in modern historiography through the study of secondary sources and art historical narratives.
Keywords: Architecture, Ottoman -- Turkey.; Architecture -- Turkey -- Istanbul.